Techniques for Dissolution and Bioavailability Enhancement of Poorly Water-Soluble Drugs - Sharma, Deepak Chandra; Gharge, Vikram; Tyagi, Prabhat (Asian Journal of Pharmaceutical Research and Development, 2021)
Solubility, the phenomenon of dissolution of solute in solvent to give a homogenous system, is one of the important parameters to achieve desired concentration of drug in systemic circulation for desired pharmacological response. Low aqueous solubility is the major problem encountered with formulation development of new chemical entities as well as for the generic development. A success of formulation development depends on how efficiently it makes the drug available at the site of action. Poorly soluble and dissolution profile creates problem in pharmaceutical industry for development of dosage form. The ability to increase aqueous solubility can thus be a valuable aid to increasing efficiency and/or reducing side effects (Adverse drug reaction) for drugs. This is true for parenterally, topically and orally administered solutions. Biopharmaceutical classification system (BCS) highlights the dissolution as rate limiting step for oral absorption of BCS class II and class IVdrugs. BCS class II and class IV drugs have low solubility.Increasing dissolution directly correlated to bioavailability of drug at site of action or systemic circulation. In this article we discuss, concept of dissolution, factors affecting dissolution,different techniques used for the enhancement of the solubility of poorly soluble drugs which include physical and chemical modifications of drug and other methods like particle size reduction, crystal engineering, salt formation, solid dispersion, use of surfactant, complexation with hydrophilic excipients.